Wellness innovations based on Bulgarian Rose (Research Announcements "Heritage BG", 2025)
Aromatherapy with Rosa Damascena, also known as Damask Rose or Bulgarian Rose, is popular for its numerous benefits. Currently, 268 studies are available in the medical database PubMed related to Rosa Damascena. These studies focus on various aspects of Rosa Damascena, including its properties, uses, and potential therapeutic effects. Researchers and scientists have conducted extensive research on this particular topic, contributing to the growing body of knowledge surrounding Rosa Damascena and its potential applications in the field of medicine. References:Enchev 1979: Enchev, Hristo. Klisura, Meditsina i fizkultura., Sofia, str. 21-25.Tisserand 1999: Tisserand, Robert. Izkustvoto na aromoterapiyata. Varna.Bikmoradi et al. 2021: Bikmoradi, Ali, Roshanaei, Ghodratollah, Moradkhani, Shirin, Fatahi, Azad. Impact of Inhalation Aromatherapy with Damask Rose (Rosa damascena) on Stress, Anxiety and Hemodynamic Parameters of Patients Undergoing Coronary Angiography: A Single-Blind Randomized Clinical Trial. Journal of complementary & integrative medicine, 19(3), 753-761. https://doi.org/10.1515/jcim-2020-0415Boskabady et al. 2011: Boskabady, Mohammad Hossein, Shafei, Mohammad Naser Saberi, Zahra, Amini, Somayeh. Pharmacological Effects of Rosa Damascena. Iranian Journal of basic medical sciences, 14(4), 295-307.Darwish et al. 2022: Darwish, Hadeer, Alharthi, Sarah, Mehanna, Radwa, Ibrahim, Samar, Fawzy, Mustafa, Alotaibi, Saqer, Albogami, Sarah, Albogami, Bander, Hassan, Sedky, Noureldeen, Ahmed. Evaluation of the Anti-Cancer Potential of Rosa damascena Mill. Callus Extracts against the Human Colorectal Adenocarcinoma Cell Line. Molecules (Basel, Switzerland), 27(19), 6241. https://doi.org/10.3390/molecules27196241Farnia et al. 2017: Farnia, Vahid, Tatari, Faeze, Alikhani, Mostafa, Shakeri, Jalal, Taghizadeh, Moshen, Karbasizadeh, Hassan, Sadeghi Bahmani, Dena, Holsboer-Trachsler, Edith, Brand, Serdge. Rosa Damascena Oil Improved Sexual Function and Testosterone in Male Patients with Opium Use Disorder under Methadone Maintenance Therapy-results from a Double-blind, Randomized, Placebo-Controlled Clinical Trial. Drug and alcohol dependence, 176, 117-125. https://doi.org/10.1016/j.drugalcdep.2017.02.008Hamedi et al. 2018: Hamedi, Somayeh, Shomali, Tahoora, Haghighat, Aliakbar. Rosa Damascena Mill. Essential Oil Has a Protective Effect Against Testicular Damage in Diabetic Rats. Journal of dietary supplements, 15(3), 311 – 317. https://doi.org/10.1080/19390211.2017.1345030Ilieva et al. 2022: Ilieva, Yana, Dimitrova, Luydmila, Georgieva, Almira, Vilhelmova-Ilieva, Nely, Zaharieva, Maya, Kokanova-Nedialkova, Zlstina, Dobreva, Ana, Nedialkov, Paraskev, Kussovski, Veselin, Kroumov, Alexsander, Najdenski, Hristo, Mileva, Milka. In Vitro Study of the Biological Potential of Wastewater Obtained after the Distillation of Four Bulgarian Oil Bearing Roses. Plants (Basel, Switzerland), 11(8), 1073. https://doi.org/10.3390/plants11081073Kalcheva 2023: Kalcheva, Hristina. Archive from Klisura Historical Museum, personal communicationMahdood et al. 2022: Mahdood, Bahareh, Imani, Behzad, Khazaei, Salman. Effects of Inhalation Aromatherapy with Rosa Damascena (Damask Rose) on the State Anxiety and Sleep Quality of Operating Room Personnel During the COVID-19 Pandemic: A Randomized Controlled Trial. Journal of perianesthesia nursing: official journal of the American Society of PeriAnesthesia Nurses, 37(4), 493 – 500. https://doi.org/10.1016/j.jopan.2021.09.011Mahmood et al. 1996: Mahmood, Naheed, Piacente, Sonia, Pizza, Cosimo, Burke, Andrew, Khan, Adil, Hay, Alan. The anti-HIV activity and mechanisms of action of pure compounds isolated from Rosa damascena. Biochemical and biophysical research communications, 229(1), 73 79. https://doi.org/10.1006/bbrc.1996.1759Marofi et al. 2015: Marofi, Maryam, Sirousfard, Motahareh, Moeini, Mahin, Gha-nadi, Alireza. Evaluation of the Effect of Aromatherapy with Rosa Damascena Mill. on Postoperative Pain Intensity in Hospitalized Children in Selected Hospitals Affiliated to Isfahan University of Medical Sciences in 2013: A Randomized Clinical Trial. Iranian journal of nursing and midwifery research, 20(2), 247-254.Mohamadi et al. 2022: Mohamadi, Neda, Pourkorrani, Mohammad, Langarizadeh, Mohammad, Ranjbartavakoli, Marziye, Sharififar, Fariba, Asgary, Sedigheh. Evidence for Rosa Damascena Efficacy in Mental Disorders in Preclinical Animal Studies and Clinical Trials: A Systematic Review. Phytotherapy research: PTR, 36(8), 3016-3031. https://doi.org/10.1002/ptr.7496Tabrizi et al. 2003: Tabrizi, Hamideh, Mortazavi, Ashrafizaadeh, Kamalinejad, Mohammad. An in vitro Evaluation of Various Rosa Damascena Flower Extracts as a Natural Antisolar Agent. International Journal of cosmetic science, 25(6), 259-265. https://doi.org/10.1111/j.1467-2494.2003.00189.xElectronic sources:https://www.thermapalace.com (visited on 03/01/2023)https://grandhotelpomorie.com (visited on 03/01/2023)https://grandhotelmillenniumsofia.bg
Keywords: Rosa Damascena; aromatherapy heritage and innovations; wellness education